Impact of biofuel production in Brazil on the economy, agriculture, and the environment - Meyer, Paula Marques; Rodrigues, Paulo H. Mazza; Millen, Danilo Domingues [UNESP] (Oxford University Press (OUP), 2013)
• Sugarcane planted area in Brazil grew by 7.56% per year during the last decade. The state of São Paulo (Southeast region) was responsible for 55.3% of all Brazilian sugarcane planted area in 2010, appreciating even more arable land values. • Consequences of the appreciation of land prices: • Rural exodus happened in almost all regions, with the greatest rate found in the Southeast region • Bovine cattle production moved toward the Midwest and North regions • Cattle industry underwent a process of intensification: around 60% of the slaughtered head growth was due to an increase in slaughter rate (slaughtered head/herd size) and 40% due to an increase in herd size, indicating that production efficiency is improving • Contribution of sugar/ethanol industry to supply co-products for cattle operations is small, and has become a recent conern for the growing livestock sector. • In the near future, livestock production, especially beef cattle, may move to other regions and promote more intensive production systems.
Keywords: Bioethanol; Cattle; Deforestation; Ethanol; Livestock; Migration; Rural exodus